Carotid Artery Corrected Flow Time and Respiratory Variations of Peak Blood Flow Velocity for Prediction of Hypotension After Induction of General Anesthesia in Adult Patients Undergoing Elective Surgery: A Prospective Observational Study. (24th October 2019) - Maitra, Souvik; Baidya, Dalim K.; Anand, Rahul K.; Subramanium, Rajeshwari; Bhattacharjee, Sulagna
Abstract : Objectives: Hypotension is common after induction of general anesthesia, and intraoperative hypotension is associated with postoperative end‐organ injury such as acute kidney injury and myocardial ischemia. This study was designed to determine the utility of the carotid corrected flow time (cFT) and carotid artery peak blood flow velocity variation (ðVpeak ) for prediction of hypotension after induction of general anesthesia. Methods: Adult patients (n = 112) undergoing any elective surgery under general anesthesia who fasted for at least 6 to 8 hours were recruited in this prospective observational study. The common carotid artery cFT and ðVpeak were measured with ultrasound 10 minutes before induction of general anesthesia. After that, general anesthesia with propofol was used, and hemodynamic data were collected until 3 minutes after induction of anesthesia. Results: The carotid cFT was significantly correlated with percentages of the fall in the systolic blood pressure at 2 minutes ( P  < .0001) and 3 minutes ( P  < .0001) and percentages of the fall in the mean arterial pressure at 1 minute ( P = .0006), 2 minutes ( P  < .0001), and 3 minutes ( P  < .0001). The cFT was a predictor of hypotension after induction of general anesthesia, with an area under the receiver operating characteristic curve of 0.91. The best cutoff value obtained from this study was 330.2 milliseconds or less, which predicted postinduction hypotension with sensitivity and specificity of 85.7% and 96.8%, respectively. The ðVpeak was an inferior predictor of postinduction hypotension, with an area under the receiver operating characteristic curve of 0.68. The optimum cutoff value was 18.8%, with sensitivity and specificity of 61.9% and 67.4%. Conclusions: The cFT measured in the common carotid artery is a reasonable predictor of hypotension after induction of general anesthesia in American Society of Anesthesiologists physical status I and II patients. Further studies are required to identify its role in high‐risk patients such as older groups and patients with cardiovascular diseases and also to identify interobserver and intraobserver variability of cFT and ðVpeak measurements.